2019
DOI: 10.1016/j.redox.2019.101275
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β-mediated Keap1-independent regulation of Nrf2 antioxidant response: A molecular rheostat of acute kidney injury to chronic kidney disease transition

Abstract: Transition of acute kidney injury (AKI) to chronic kidney disease (CKD) represents an important cause of kidney failure. However, how AKI is transformed into CKD remains elusive. Following folic acid injury, mice developed AKI with ensuing CKD transition, featured by variable degrees of interstitial fibrosis and tubular cell atrophy and growth arrest. This lingering injury of renal tubules was associated with sustained oxidative stress that was concomitant with an impaired Nrf2 antioxidant defense, marked by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 77 publications
0
64
0
Order By: Relevance
“…Under basal conditions, KEAP1 binds and sequesters NRF2 in cytoplasm for proteasome degradation, whereas NRF2 can evade the repression of KEAP1 and translocate into nucleus to initiate the transcription of target genes 11 . Apart from KEAP1, NRF2 can be regulated by other factors 12,13 , such as WDR23-DDB1-CUL4 regulatory axis 14 and miRNAs related mechanisms 15,16 . Recent study has shown that NRF2 is the main target of radiosensitive agent salinomycin in NPC cells 17 , however, the expression pattern of NRF2, and its activation mechanism in NPC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Under basal conditions, KEAP1 binds and sequesters NRF2 in cytoplasm for proteasome degradation, whereas NRF2 can evade the repression of KEAP1 and translocate into nucleus to initiate the transcription of target genes 11 . Apart from KEAP1, NRF2 can be regulated by other factors 12,13 , such as WDR23-DDB1-CUL4 regulatory axis 14 and miRNAs related mechanisms 15,16 . Recent study has shown that NRF2 is the main target of radiosensitive agent salinomycin in NPC cells 17 , however, the expression pattern of NRF2, and its activation mechanism in NPC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In cisplatin-AKI, DMF also reduced peritubular fibrosis [ 184 ]. In a mouse model of folic acid-induced AKI, specific deletion of GSK3β in renal tubules or treatment with a GSK3β inhibitor improved the Nrf2 antioxidant response, independently of Keap1, protecting from AKI to CKD transition [ 185 ].…”
Section: Nrf2 and Akimentioning
confidence: 99%
“…Because of persistent oxidative stress, the cell programs its death by apoptosis to prevent degeneration and proliferation in an uncontrollable way 14 . Activation of Nrf2 can alleviate the toxicity related to reactive oxygen species and is an important molecular target for the prevention of renal injury 15 .…”
Section: Introductionmentioning
confidence: 99%